On Government Centralization and Fiscal Referendums: A Theoretical Model and Evidence from Switzerland - Lars P. Feld; Christoph A. Schaltegger; Jan Schnellenbach (Center for Research in Economics, Management and the Arts (CREMA), 2005)
We propose and test a positive model of fiscal federalism in which centralization is less likely to occur in jurisdictions with referendum decisions on policy cen-tralization. Citizens choose centralization of public spending and revenue in order to internalize spillovers if individual preferences in two jurisdictions are suffi-ciently homogeneous. Under representative democracy, centralization is ineffi-ciently high because representatives can extract political rents by policy centrali-zation. Referendums thus restrict representatives' ability for rent extraction. An empirical analysis using a panel of Swiss cantons from 1980 to 1998 supports the hypothesis that centralization is less likely under referendum decision-making.
Keywords: H1; H7; D72; 330; Centralization; Fiscal Federalism; Fiscal Referendums